The Transformation of Pesantren Education Quality Management in the Digital Era: An Integrative Literature Review - Ifan Syafiuddin; Sabiila Khoirin Ni'mah; Uswatun Khasanah; Hasan Darajat (Jurnal Ilmiah Guru Madrasah, 2026)
Digital transformation is changing how pesantren manage learning, administration, and institutional accountability while raising concerns about the continuity of religious authority and educational traditions. This study examines the transformation of pesantren education quality management and formulates a context-sensitive framework for the digital era. It uses a structured integrative literature review organized through the Search, Appraisal, Synthesis, and Analysis (SALSA) framework. The final analytical corpus consisted of 27 substantive sources, including journal articles, foundational and conceptual works, and policy or institutional documents selected for their relevance, transparency, contextual fit, and verifiability. The synthesis identifies five drivers of transformation, six recurring challenges, and eight interrelated management dimensions. Spiritual and ethical values form the framework’s normative foundation; value-grounded leadership, sustainable quality culture, and contextual internal quality assurance constitute its governance layer; and selective digitalization, human resource and digital competence development, curriculum integration, and strategic collaboration form its operational layer. The framework treats technology as wasilah (a means) for educational purposes rather than an end in itself. Because it is derived from an integrative review, the framework represents conceptual relationships rather than empirically established causal effects. Comparative empirical research is required before its effectiveness can be assessed across different pesantren contexts.